2011
DOI: 10.1007/s13355-011-0085-3
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of salicylic acid, jasmonic acid and phytoalexins in rice, Oryza sativa, infested by the white-backed planthopper, Sogatella furcifera (Hemiptera: Delphacidae)

Abstract: In order to clarify the mechanism of induced resistance to blast disease in rice, Oryza sativa, that had been previously infested by the white-backed planthopper, Sogatella furcifera Horváth, we first investigated the accumulation of salicylic acid (SA) and jasmonic acid (JA) in rice plants infested by the planthopper. The results confirmed that infestation of S. furcifera strongly stimulates the production of SA and JA in rice. These results indicate that both salicylate-and jasmonate-mediated pathways (SA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 45 publications
1
48
1
Order By: Relevance
“…[1][2][3] It is also well known that JA plays an important role in rice defense responses. [4][5][6][7][8] In addition, it has been revealed that JA treatment causes the accumulation of plant volatile compounds in rice. [9][10][11] Plant volatile compounds, such as terpenoids and C 6 volatiles, are emitted from microbe-infected or wounded plant sites, and are potential signal compounds that induce defenses against tissue damage from herbivores and plant pathogens.…”
mentioning
confidence: 99%
“…[1][2][3] It is also well known that JA plays an important role in rice defense responses. [4][5][6][7][8] In addition, it has been revealed that JA treatment causes the accumulation of plant volatile compounds in rice. [9][10][11] Plant volatile compounds, such as terpenoids and C 6 volatiles, are emitted from microbe-infected or wounded plant sites, and are potential signal compounds that induce defenses against tissue damage from herbivores and plant pathogens.…”
mentioning
confidence: 99%
“…Normally, the high amount of phytoalexin was found close to damaged area from the disease attack (Großkinsky et al, 2012). Phytoalexins would directly damage cell wall of intruding microorganisms by inhibiting growth, interfering metabolism and retarding colonizing process of pathogenic disease (Kanno et al, 2012). This experiment showed that after rice leaves were clipped and inoculated by Xanthomonas oryzae pv.…”
Section: Discussionmentioning
confidence: 92%
“…oryzae (c). under abiotic and biotic (Dillon et al, 1997;Liu et al, 2012;Kanno et al, 2012), depend on type of stress. In this experiment the results showed that ozone had more capacity to induce sakuranetin rather than momilactone A.…”
Section: Discussionmentioning
confidence: 99%
“…According to Yang et al (2004), rice had two orders of magnitude higher levels of SA than tobacco and Arabidopsis, and was insensitive to exogenous SA. In addition, Kanno et al (2012) reported that JA and SA contents in rice leaves were increased by the feeding damage of white-back planthopper (Sogatella furcifera), but the increment of SA was less than that of JA because rice plants contain much higher levels of endogenous SA in healthy tissues. Therefore, we conclude that the role of SA in rice is less pronounced than in other plants, and that JA and ethylene are major components of signal transduction causing O 3 injury.…”
Section: Discussionmentioning
confidence: 99%